ANALISIS KOMPETENSI PENGOPERASIAN ALAT TRANSAKSI CASH REGISTER SISWA KELAS XI PEMASARAN - Mutia, Utin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is aims to understand analysis competence the operation of instrument transactions a cash register students in XI marketing class SMKN 1 Pontianak .Methods used in research this is the method descriptive with the form of the research survey and using a qualitative approach . Data sources in this research was 9 respondents consisting of 8 students and teachers 1. Data were collected by using guidelines observation and guidelines as well as the results of sheets note and documentation. The research results show that competence students who when viewed from the aspect knowledge students has been good enough , aspects skill is quietly still weak because students must not to have received matter sufficient and lack of empowerment from teachers , and facets attitude students enough well even though in terms of interest students not good. Based on the results of research conducted in SMKN 1 Pontianak. Researcher give advice that teachers hold an internship before industrial work practices at least one week so that students knew well steps prior preparation used a transaction a cash register because the procedure is very important in the operation of instrument transactions a cash register.Keywords: Competence, The Operation of Instrument Transactions, Cash Register